2018
DOI: 10.1074/mcp.ra118.001036
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Secretome Analyses of Human and Zoonotic Staphylococcus aureus Isolates CC8, CC22, and CC398

Abstract: The proteogenomes and secretomes of dominant human and zoonotic S. aureus lineages CC8, CC22 and CC398 were compared revealing genomic and regulatory differences in the secretion of 869 proteins. In the core secretome, 101 secreted or cell surface anchored virulence factors contribute with 82.4% to total secretome abundance. CC398 isolates showed higher secretion of α- and ß-hemolysins and lower secretion of surface proteins resulting in strong hemolysis and decreased biofilm formation because of lower SigB ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 114 publications
(201 reference statements)
2
31
0
Order By: Relevance
“…It could be related to the mode of transmission, with close contact with animals. In contrast, fewer cases of MSSA CC398 RTI have been reported [7,8,16,19,20,27,29,37,39,50,55,61,62,68,74]. Hence, a French study of 89 clinical isolates of MSSA CC398 reported that 12% were isolated from pneumonia, 22% from BSI and 29% from SSTI [19].…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%
“…It could be related to the mode of transmission, with close contact with animals. In contrast, fewer cases of MSSA CC398 RTI have been reported [7,8,16,19,20,27,29,37,39,50,55,61,62,68,74]. Hence, a French study of 89 clinical isolates of MSSA CC398 reported that 12% were isolated from pneumonia, 22% from BSI and 29% from SSTI [19].…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%
“…Many studies have used liquid culture medium to identify the secretome from pathogenic microbes, eg. Xanthomonas oryzae, Botrytis cinerea , and Staphylococcus aureus [34-37]. In the present study, we used a quantitative proteomics approach to analyze the secretome of M. oryzae and identified 558 proteins from the liquid culture medium, including 411 proteins of the wild-type P131 strain and 539 proteins of the Δ alg3 mutant strain.…”
Section: Discussionmentioning
confidence: 99%
“…Hla is secreted by approximately 95% of clinical S. aureus strains, with observable trends in distinct clonal types, such as an increase in Hla expression in CC398 strains, which correlates with stronger hemolysin activity [ 6 ]. Interestingly, CC398 is a commonly identified lineage of livestock-associated MRSA that can infect pigs as well as humans.…”
Section: Role Of S Aureus Toxins In Human Disementioning
confidence: 99%
“…This study found that LA-MRSA isolates are highly cytotoxic in comparison with human HA- and CA-MRSA isolates but are less adherent to human cells than human isolates. All tested LA-MRSA CC398 strains also expressed hla when tested by qRT-PCR [ 6 , 7 ]. Hla has been notably associated with colonization of individuals who go on to develop invasive disease.…”
Section: Role Of S Aureus Toxins In Human Disementioning
confidence: 99%